How environmental literacy research works in biology learning? A literature review - Jundi Awaludin; Tri Handayani Kurniati; Rizhal Hendi Ristanto; Ratna Komala (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Environmental problems are a factor that influences the health of the world's great population. Developed countries make pollution part of a serious problem in urban industrial centers. The aim of this research is to address the following objectives: (1) to analyze the trend in the number of environmental literacy research conducted annually; (2) to identify the methodologies employed in investigating environmental literacy in Indonesia; (3) to determine the demographics of research subjects involved in studies related to environmental literacy; (4) to ascertain the geographic locations utilized as research sites for studies concerning environmental literacy. This research focuses on content analysis that has been determined from various research published in scientific journals in Indonesia and international journals. In this research, the focus is on articles discussing environmental literacy in Indonesian journals indexed by SINTA. There are 24 articles discussing environmental literacy. positive trends were found in research related to environmental literacy. Among these articles, quantitative research is often found. The samples found in the article were mostly found in junior high schools. Apart from that, the data collection used was a test instrument. and most often use independently composed instruments. In light of the findings of this study, several recommendations have been made for further research.